2019
DOI: 10.1038/s41598-019-53862-3
|View full text |Cite
|
Sign up to set email alerts
|

A Simulated Microgravity Environment Causes a Sustained Defect in Epithelial Barrier Function

Abstract: Intestinal epithelial cell (IEC) junctions constitute a robust barrier to invasion by viruses, bacteria and exposure to ingested agents. Previous studies showed that microgravity compromises the human immune system and increases enteropathogen virulence. However, the effects of microgravity on epithelial barrier function are poorly understood. The aims of this study were to identify if simulated microgravity alters intestinal epithelial barrier function (permeability), and susceptibility to barrier-disrupting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 93 publications
1
19
0
1
Order By: Relevance
“…The duration that cells were exposed to simulated microgravity is an important experimental variable, which can range from 1 hour 116 to over 14 days. 105 There is increasing evidence that simulated microgravity exerts temporal effects due to cellular adaptation. For example, prolonged exposure to simulated microgravity (between 2 and 14 days) was shown to reduce dendritic T cell activation whereas short term exposition (<72 hours) increased dendritic cell maturation markers.…”
Section: Duration Of Simulated Microgravity Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…The duration that cells were exposed to simulated microgravity is an important experimental variable, which can range from 1 hour 116 to over 14 days. 105 There is increasing evidence that simulated microgravity exerts temporal effects due to cellular adaptation. For example, prolonged exposure to simulated microgravity (between 2 and 14 days) was shown to reduce dendritic T cell activation whereas short term exposition (<72 hours) increased dendritic cell maturation markers.…”
Section: Duration Of Simulated Microgravity Exposurementioning
confidence: 99%
“…This can significantly reduce autocrine signaling and may be another factor behind apoptosis and lower cell numbers typically reported in simulated microgravity studies. For example, RWV (full vessel) culture of intestinal epithelial cells was shown to disrupt intestinal epithelial barrier integrity 105 and increased culture medium volume was found to reduce osteoblast fusion and mineralization (bone formation) 106 . In paracrine studies, cell‐conditioned medium extracted from s‐μg culture was reported to have a cross‐pathogenic effect on endothelial cell and smooth muscle cell proliferation and migration compared to normal gravity‐conditioned medium 107 .…”
Section: Cell Signaling and The Culture Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Igualmente existen alteraciones en la motilidad, microbiota intestinal, metabolismo de glucosa y lípidos (89,90) , daño de las vellosidades intestinales e interrupción en las uniones celulares epiteliales por la expresión de la proteína proapoptótica Bax y disminución de Bcl2; alterando de esta manera su función defensiva, homeostasis y el riesgo de contraer enfermedades inflamatorias intestinales (76,91,92,93) por el aumento de citosinas y disminución de la inmunoglobulina secretora (IgA) (76) .…”
Section: Sistema Digestivounclassified
“…Professor McCole's group, together with Dr Kim Prisk, investigated the previously little-understood effects of microgravity (low gravity environments, as would be experienced in outer space) on the epithelial cell barrier (5). Previous studies in the field of space biology have demonstrated that microgravity can have a negative impact on the human immune system, via suppression of multiple immune cells.…”
Section: Microgravitymentioning
confidence: 99%